(1)∵ 4 S n =
a 2n +2 a n +1 ,
∴当n≥2时, 4 S n-1 =
a 2n-1 +2 a n-1 +1 .
两式相减得 4 a n =
a 2n -
a 2n-1 +2 a n -2 a n-1 ,
∴(a n+a n-1)(a n-a n-1-2)=0
∵a n>0,∴a n-a n-1=2,
又 4 S 1 =
a 21 +2 a 1 +1 ,∴a 1=1
∴{a n}是以a 1=1为首项,d=2为公差的等差数列.
∴a n=a 1+(n-1)d=2n-1;
(2)由(1)知 S n =
(1+2n-1)n
2 = n 2 ,
假设正整数k满足条件,
则(k 2) 2=[2(k+2048)-1] 2
∴k 2=2(k+2048)-1,
解得k=65;
(3)证明:由 S n = n 2 得: S m = m 2 , S k = k 2 , S p = p 2
于是
1
S m +
1
S p -
2
S k =
1
m 2 +
1
p 2 -
2
k 2 =
k 2 ( p 2 + m 2 )-2 m 2 p 2
m 2 p 2 k 2
∵m、k、p∈N *,m+p=2k,
∴
k 2 ( p 2 + m 2 )-2 m 2 p 2
m 2 p 2 k 2
=
(
m+p
2 ) 2 ( p 2 + m 2 )-2 m 2 p 2
m 2 p 2 k 2 ≥
mp×2pm-2 m 2 p 2
m 2 p 2 k 2 =0 .
∴
1
S m +
1
S p ≥
2
S k .